2020
DOI: 10.1186/s12889-020-8188-9
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a community cardiovascular disease prevention programme in Mukono and Buikwe districts in Uganda: a qualitative study

Abstract: Background: Cardiovascular diseases (CVDs) are on the rise in many low-and middle-income countries where 80% of related deaths are registered. Community CVD prevention programmes utilizing self-care approaches have shown promise in contributing to population level reduction of risk factors. However, the acceptability of these programmes, which affects their uptake and effectiveness, is unknown including in the sub-Saharan Africa context. This study used the Theoretical Framework of Acceptability to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 36 publications
4
27
0
1
Order By: Relevance
“…As such, street children must dully navigate the challenges of migration while adapting to the new street culture, new language and socio-emotional culture (49)(50). Studies elsewhere have yielded similar results with limited access to health and reproductive care services reported among the urban rural youth, migrant sex workers and out-of-school adolescents (38) (51).…”
Section: Association Between Migration and Srh Service Uptakesupporting
confidence: 66%
See 1 more Smart Citation
“…As such, street children must dully navigate the challenges of migration while adapting to the new street culture, new language and socio-emotional culture (49)(50). Studies elsewhere have yielded similar results with limited access to health and reproductive care services reported among the urban rural youth, migrant sex workers and out-of-school adolescents (38) (51).…”
Section: Association Between Migration and Srh Service Uptakesupporting
confidence: 66%
“…show that 61.99% (n=318) of the street children had received at least one component of the SRH services in the last twelve months while 11.50% (n=29) had received all the three SRH services (STI screening, HIV testing & FP use). Across all the SRH service components, use of services was generally lower among migrant compared to the non-migrant street children, with51.76% migrants having ever tested for HIV in the past 12 months compared to 67.25% of the lifelong native street children; use of any modern family planning method was low with 14.14% of migrant street children compared to 22.71% of non-migrant street children. Similarly, prevalence of STI screening was lower for migrant street children compared to lifelong native street children.…”
mentioning
confidence: 94%
“…Over 80% of our respondent households had a mobile phone whose ownership was associated with being knowledgeable thus increasing the potential for mobile health interventions, which have shown promise for CVD prevention in low- and middle- income countries [ 26 , 27 ]. Also, although community health workers were a less reported avenue for advice, our previous research has shown that they are acceptable [ 28 ] and thus could be a key resource to target to improve community awareness on CVD especially in low income settings through their routine health promotion activities. Indeed, systematic reviews have demonstrated that community health workers could be effective in tackling the burden of CVD in both low- and- middle income countries [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, community approaches have been successful in supporting infectious disease control efforts and improvement of health outcomes in SSA [16,17]. However, there is limited evidence of replication of similar efforts for NCDs even with increasing evidence of the acceptability of such programmes [18].…”
Section: Introductionmentioning
confidence: 99%